Biochemical and clinical aspects of glycogen storage diseases. Issue 3 (September 2018) - Ellingwood, Sara S; Cheng, Alan
Abstract : The synthesis of glycogen represents a key pathway for the disposal of excess glucose while its degradation is crucial for providing energy during exercise and times of need. The importance of glycogen metabolism is also highlighted by human genetic disorders that are caused by mutations in the enzymes involved. In this review, we provide a basic summary on glycogen metabolism and some of the clinical aspects of the classical glycogen storage diseases. Disruptions in glycogen metabolism usually result in some level of dysfunction in the liver, muscle, heart, kidney and/or brain. Furthermore, the spectrum of symptoms observed is very broad, depending on the affected enzyme. Finally, we briefly discuss an aspect of glycogen metabolism related to the maintenance of its structure that seems to be gaining more recent attention. For example, in Lafora progressive myoclonus epilepsy, patients exhibit an accumulation of inclusion bodies in several tissues, containing glycogen with increased phosphorylation, longer chain lengths and irregular branch points. This abnormal structure is thought to make glycogen insoluble and resistant to degradation. Consequently, its accumulation becomes toxic to neurons, leading to cell death. Although the genes responsible have been identified, studies in the past two decades are only beginning to shed light into their molecular functions.